2012
DOI: 10.1100/2012/361382
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor and Immunopotentiating Activity of Polysaccharide PST001 Isolated from the Seed Kernel ofTamarindus indica: An In Vivo Study in Mice

Abstract: Antitumor activity of polysaccharide PST001 isolated from the seed kernel of Tamarindus indica was evaluated using different cancer cell lines. Human cancer cell lines A549, KB, and MCF-7 and murine cancer cell lines DLA and EAC were treated with PST001 and cell growth inhibition was assessed by MTT assay. In vivo studies were carried out for toxicity, tumor reduction and immunomodulation. The respective IC50 of PST001 in A549, KB, and DLA was at 80.72, 190.99, and 91.14 μg/mL. Significant tumor reduction was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 16 publications
1
51
0
Order By: Relevance
“…After considering the potent effects of PST-Dox on cancer cells, we next aimed at evaluating for any toxic effects in normal lymphocytes. Previously, it has been reported that the parent polymer PST001 does not elicit any notable toxic effects in normal cells in vitro and in vivo [14,15]. In line with this observation, we presumed that PST-Dox would not have serious deleterious effects on normal cells.…”
Section: Anticancer Effects Of Pst-dox Nanoparticlessupporting
confidence: 71%
See 2 more Smart Citations
“…After considering the potent effects of PST-Dox on cancer cells, we next aimed at evaluating for any toxic effects in normal lymphocytes. Previously, it has been reported that the parent polymer PST001 does not elicit any notable toxic effects in normal cells in vitro and in vivo [14,15]. In line with this observation, we presumed that PST-Dox would not have serious deleterious effects on normal cells.…”
Section: Anticancer Effects Of Pst-dox Nanoparticlessupporting
confidence: 71%
“…The detailed isolation protocol was followed as reported earlier [15,18]. Carbohydrate content was determined colorimetrically by phenol-sulfuric acid method of Dubois [20].…”
Section: Synthesis and Characterization Of Pst-dox Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Its seeds are often considered useless and wasted by the common household because of their flavorless and brittle consistency. Various chemical laboratories around the world inquisitively have found a rich presence of various amino acids, flavonoids, polyphenols, and other biological essentials within the seeds (11) and have advocated their anticancer and anti-stress potentials (11,13,(16)(17)(18)(19)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Presence of different compounds makes different parts of the plant unique in function. While the leaf extract of TI had anti-apoptotic effects (13), its whole-seed, seed-kernel-derived and seed-coat-derived extracts had antioxidant (21), cytotoxic (22), and immuno-protective (23,24,25) effects, respectively. In the present study, we have prepared the aqueous and ethanol extracts of tamarind seeds, and examined their cytotoxicity, anti-stress and anti-melanogenesis properties by human cell-based assays.…”
Section: Introductionmentioning
confidence: 99%